Non-invasive Beta-cell Imaging: Visualization, Quantification, and Beyond - Murakami, Takaaki; Fujimoto, Hiroyuki; Inagaki, Nobuya (Frontiers in Endocrinology, 2021)
Pancreatic beta (β)-cell dysfunction and reduced mass play a central role in the development and progression of diabetes mellitus. Conventional histological β-cell mass (BCM) analysis is invasive and limited to cross-sectional observations in a restricted sampling area. However, the non-invasive evaluation of BCM remains elusive, and practical in vivo and clinical techniques for β-cell-specific imaging are yet to be established. The lack of such techniques hampers a deeper understanding of the pathophysiological role of BCM in diabetes, the implementation of personalized BCM-based diabetes management, and the development of antidiabetic therapies targeting BCM preservation and restoration. Nuclear medical techniques have recently triggered a major leap in this field. In particular, radioisotope-labeled probes using exendin peptides that include glucagon-like peptide-1 receptor (GLP-1R) agonist and antagonist have been employed in positron emission tomography and single-photon emission computed tomography. These probes have demonstrated high specificity to β cells and provide clear images accurately showing uptake in the pancreas and transplanted islets in preclinical in vivo and clinical studies. One of these probes, 111indium-labeled exendin-4 derivative ([Lys12(111In-BnDTPA-Ahx)]exendin-4), has captured the longitudinal changes in BCM during the development and progression of diabetes and under antidiabetic therapies in various mouse models of type 1 and type 2 diabetes mellitus. GLP-1R-targeted imaging is therefore a promising tool for non-invasive BCM evaluation. This review focuses on recent advances in non-invasive in vivo β-cell imaging for BCM evaluation in the field of diabetes; in particular, the exendin-based GLP-1R-targeted nuclear medicine techniques.